Investigation on corrosion and interface conductivity of TA1 under dynamic loads in proton exchange membrane water electrolyzer anodic environment - Huang, Yao; Li, Lin; Yao, Jizheng; Zhang, Gaoqun; Deng, Zhanfeng; Zhang, Bin (Frontiers in Energy Research, 2024)
In this paper, the electrochemical and corrosion behavior of pure titanium (TA1) in simulated Proton Exchange Membrane Water Electrolysis (PEMWE) anodic environment was investigated. In this condition, the corrosion potential of TA1 was -689 mV, with a self-corrosion current density of 232.5 μA•cm -2 , and a polarization resistance of 125.9 Ω•cm 2 . During potentiostatic polarization at 2 V, the current density was maintained at approximately 6 mA•cm -2 . However, the passivation process exhibited instability. Furthermore, this process has been shown to significantly facilitate the formation of surface oxides, and the passive film that formed displays the lowest bound water and OH -, and the highest content of O 2-, exhibiting the highest average valence. Notably, dynamic potentials caused current transients, among which square wave potential was the most remarkable. the square wave potential shows an O 2-content just below that of 2V potential polarization when fluctuating potentials are applied. The interfacial contact resistance (ICR) of 2 V potentiostatic polarization was slightly higher than that of square, sine and triangular waves. Additionally, the high temperature condition of PEMWE will aggravate the corrosion of TA1 by fluoride ions.